Strategies for involving patients and the public in scaling initiatives in health and social services: A scoping review - Roberta deCarvalho Corôa; Ali Ben Charif; Vincent Robitaille; Diogo G. V. Mochcovitch; Mamane Abdoulaye Samri; Talagbe Gabin Akpo; Amédé Gogovor; Virginie Blanchette; Lucas Gomes Souza; Kathy Kastner; Amélie M. Achim; Robert K. D. McLean; et al. (Health Expectations)
Abstract Background Scaling in health and social services (HSS) aims to increase the intended impact of proven effective interventions. Patient and public involvement (PPI) is critical for ensuring that scaling beneficiaries’ interests are served. We aimed to identify PPI strategies and their characteristics in the science and practice of scaling in HSS. Methods In this scoping review, we included any scaling initiative in HSS that used PPI strategies and reported PPI methods and outcomes. We searched electronic databases (e.g., Medline) from inception to 5 February 2024, and grey literature (e.g., Google). Paired reviewers independently selected and extracted eligible reports. A narrative synthesis was performed and we used the PRISMA for Scoping Reviews and the Guidance for Reporting Involvement of Patients and the Public (GRIPP2). Findings We included 110 unique reports out of 24,579 records. In the past 5 years, the evidence on PPI in scaling has increased faster than in any previous period. We found 236 mutually nonexclusive PPI strategies among 120 scaling initiatives. Twenty‐four initiatives did not target a specific country; but most of those that did so (n = 96) occurred in higher‐income countries (n = 51). Community‐based primary health care was the most frequent level of care (n = 103). Mostly, patients and the public were involved throughout all scaling phases (n = 46) and throughout the continuum of collaboration (n = 45); the most frequently reported ethical lens regarding the rationale for PPI was consequentialist‐utilitarian (n = 96). Few papers reported PPI recruitment processes (n = 31) or incentives used (n = 18). PPI strategies occurred mostly in direct care (n = 88). Patient and public education was the PPI strategy most reported (n = 31), followed by population consultations (n = 30). Conclusions PPI in scaling is increasing in HSS. Further investigation is needed to better document the PPI experience in scaling and ensure that it occurs in a meaningful and equitable way. Patient and Public Contribution Two patients were involved in this review. They shared decisions on review questions, data collection instruments, protocol design, and findings dissemination. Review Registration Open Science Framework on 19 August 2020 (https://osf.io/zqpx7/).